LONG-TERM SELF-MANAGEMENT OF VAGINAL CUBE PESSARIES CAN IMPROVE SEXUAL LIFE IN PATIENTS WITH PELVIC ORGAN PROLAPSE - SAIFULLAH, S; HASHMI, A; ARA, F; SHOAIB, M; IRAM, R; MARYAM, . (Biological and Clinical Sciences Research Journal, 2024)
Pelvic organ prolapse (POP) is a widespread health issue that affects a significant proportion of women, particularly those who have experienced childbirth, undergone hysterectomy, or are postmenopausal. Objective: This study employs a secondary analysis to explore the long-term self-management of vaginal cube pessaries and its potential impact on sexual health in women with pelvic organ prolapse (POP). Methods: The retrospective observational study was conducted at Sandeman Provincial Hospital in Quetta from 01 August 2022 to 31 July 2023. The sample consists of 100 women diagnosed with pelvic organ prolapse who were treated with vaginal cube pessaries. Data was collected from the clinical records of patients who were part of the hospital’s pessary management program during the study period. Results: Data were collected from 100 participants. The majority of participants in this study were between the ages of 50 and 69 years (65%), with 75% of the women being postmenopausal. A significant portion of the population (60%) had more than two children, which is a common risk factor for pelvic organ prolapse. Most of the participants were diagnosed with moderate to severe prolapse, with 45% in Stage II and 30% in Stage III, indicating that the sample represents a range of prolapse severity, including advanced cases (Stage IV, 15%). Patient satisfaction with pessary self-management was generally high, with 50% of participants being highly satisfied and 30% moderately satisfied. Only 20% expressed dissatisfaction, which suggests that most women found self-managing their pessaries to be beneficial. Conclusion: This study concludes that long-term self-management of vaginal cube pessaries significantly improves sexual function and overall quality of life in women with pelvic organ prolapse.